Differences in Students' Scientific Literacy Abilities in Solving Story Questions on Environmental Change Material in Class X of SMA in Ambon City - Nanda, Dea Ariska; Tuaputty, Hasan; Smith, Alwi (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
Scientific literacy began to emerge since the implementation of the Program for International Student Assessment (PISA) in Indonesia. Since Indonesia's participation in the Program for International Student Assessment (PISA) in 2000, Indonesia has always been at the bottom of the rankings..This research aims toanalyzestudents' scientific literacy abilities in solving story questions on environmental change material in class X SMA in Ambon City andto knowdifferences in students' scientific literacy abilities in solving story questions on environmental change material in class X SMA in Ambon City. This type of research ismix method. The research population, namelySMA Negeri 3 Ambon, SMA Negeri 5 Ambon and SMA Negeri 11 Ambonwith a total sample of 103 students. The research instruments used were tests and interview instruments. Data analysis techniques using Independent Sample T Test with SPSS Version 27 software.The research results show that Students' scientific literacy abilities are quite good at SMAN 11 Ambon, and there is a difference in students' scientific literacy abilities in solving story questions on environmental change material in class is 0.000 < 0.05 and group SMAN 5 with SMAN 11 0.003 < 0.05